Pengabdian Masyarakat Untuk Meningkatkan Pengetahuan Dan Keterampilan Masyarakat Dalam Pengelolaan Sampah Rumah Tangga Menjadi Bahan Bernilai Ekonomis Di Desa Talimbaru Kecamatan Barusjahe Kabupaten Karo - Deli Syaputri; Susanti Br Perangin Angin; Samuel Marganda H Manalu; Mustar Rusli; Th.Teddy BS (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Household waste is an environmental problem that continues to increase along with population growth and changes in people's lifestyles. Based on data from the Ministry of Environment and Forestry (KLHK) in 2023, Indonesia produces around 67.8 million tons of waste annually, of which around 37.3% comes from household waste. Ironically, most of this waste has not been managed properly, causing various negative impacts, such as environmental pollution, health problems, and disasters such as floods. Household waste management remains a problem in Talimbaru Village, Barusjahe District, Karo Regency due to the community's lack of knowledge in sorting and utilizing waste. This community service activity aims to improve community knowledge, attitudes, and actions through counseling and training on managing organic and inorganic waste into economically valuable products. The methods used include counseling, demonstrations of composting and ecobrick making, hands-on practice, and evaluation using pre-tests and post-tests for 80 participants. The results of the activity showed an increase in community knowledge from the majority in the low category to all participants in the high category after the training. Positive attitudes and community actions regarding waste management have also increased, marked by the implementation of waste sorting, composting, and the utilization of plastic waste to create ecobricks. These activities effectively increase community capacity in household waste management and support the creation of a cleaner, healthier, and more economically valuable environment.